Independence celebrations in Honduras (1821-1921): a Foucaultian perspective - Cardona Amaya, José Manuel (2025)
Introduction: This article examines the historical development of Honduras’s independence celebrations between 1821 and 1921, from the first events promoted by Juan Lindo to the centennial of emancipation. Through the analysis of decrees, official programs, and press reports, it interprets the civic ritual as a device of power that articulated religion, politics, and education in the making of the modern state. Objective: To analyze how the September 15th ceremony evolved from a local custom into a state practice of government aimed at shaping collective behavior and producing patriotic subjectivity. Method and technique: The research combines the historical method with a genealogical reading based on Michel Foucault’s concepts of power, governmentality, and technologies of the self. Primary sources—decrees, newspapers, and official programs—are interpreted through the lens of ritual analysis and governmentality studies. Results: The study identifies three stages in the evolution of the celebration: a foundational phase (1848–1882), a transitional one (1883–1894), and a liberal consolidation phase (1894–1921). Each reflects a shift of power from religious devotion to civic education as a symbolic form of control. Conclusions: Independence celebrations became a technology of government that reproduced state authority through patriotic emotion, ritual repetition, and the symbolic occupation of public space.